(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
Abstract: Uzbekistan is an important country for China’s economic and trade cooperation in Central Asia, and deepening cooperation between China and Uzbekistan has strategic significance. In recent years, bilateral trade volume has steadily increased, and the scale of economic and technological cooperation has continued to expand. However, there are also constraints such as poor transportation and relatively bad investment environment. However, with the continuous close cooperation between two countries, there is still enormous potential for economic cooperation between China and Uzbekistan.